Renal Functional Status of Asphyxiated Babies & its Correlation with Apgar Score - Saha, Dipa; Mollah, Md Abid Hossain; Afroz, Shireen; Banerjee, Manisha; khan, Tofazzal H; Saha, Chinmoy Sumar (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Introduction: Kidney is the 2nd commonest affected organ as a consequence of asphyxia1. Most attention is given to prevent CNS damage and neurological sequel but hypoxic renal insult not only influences neonatal morbidity & mortality but may give rise to CKD. to assess the renal functional status of asphyxiated babies. Material & Methods: This cross sectional study was conducted in the Department of Neonatology & Department of Gynecology and Obstetrics, Dhaka Medical College Hospital during January 2012 to January 2013. A total of 150 inborn, term asphyxiated neonates with e 2.5 kg who had history of delayed or no cry with Apgar score <7 at 5 minutes were enrolled. Then, the cases were grouped into mild (AS: 6-7), moderate (AS: 4-5) and severe asphyxia (AS: 0-3) based on Apgar score. Forty eight neonates were excluded according to exclusion criteria. Finally, the renal functions were assessed among 102 neonates by measuring urine output 8 hourly and estimated creatinine clearance (eCCL) on the 3rd day o7f life using Schwartz formula (eCCl=Height (cm) ×.37/S.creatinine). Neonates with impaired renal function were further classified as stage-I (risk), II (injury), III (failure) using pRIFLE criteria. Data were analyzed by Chi-square & Pearson correlation coefficient test to find out correlation between Apgar scores and renal functional status. Results: Of the 102 cases studied, majority 48% were in moderate, 30.4% in mild and 21.6% in severely asphyxiated group. In the mild asphyxiated group 58.06% had normal renal function. However, the remaining cases 29.03% & 12.90% had stage I, stage II renal injury respectively and had no renal failure. In Moderately asphyxiated group, 26.53% had normal renal function & the remaining 32.65%, 34.69%, 6.1% had stage I, II, III renal injury respectively. None of the severely asphyxiated babies had normal renal function. However they had impaired renal function ranging from Stage I (27.27%), stage II (27.27%) & stage III (40.90%).Variable proportion of kidney injuries were noted among the asphyxiated neonates. The lower the Apgar score, the more severe the injuries and association between stages of kidney injuries and Apgar score was observed statistically significant (p<0.001). The renal functional status (eCCL) was also found positively correlated with low Apgar score (r=0.6, p<0.002). Conclusion: Variable functional impairment of kidneys was found among the asphyxiated neonates and the severity of impairment significantly correlated with low Apgar score. J Bangladesh Coll Phys Surg 2017; 35(3): 128-132